Pengaruh Likuiditas, Profitabilitas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Sektor Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022) - Emillia Titin Fatmawati; Rispantyo (CV. ITTC INDONESIA, 2024)
Company value is a concept that investors consider when evaluating their investments, and is an indicator of how the market values a company as a whole. The purpose of this study is to determine the significance of Liquidity, Profitability, and Company Size to Company Value. This study uses a type of quantitative data with the data source used as secondary data, namely the annual report accessed through the official website of the Indonesia Stock Exchange for the 2019-2022 period. The population of this study is 84 companies and the sampling method uses the purposive sampling technique so that the number of samples that meet the criteria is 20 companies. The data collection method used is by documentation technique. The analysis techniques used are descriptive statistical tests and multiple linear regression analysis. The results of the study found that liquidity had a significant negatif effect on company value, profitability had a significant positif effect on company value and company size did not affect company value in property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2022 period.